Successful Use of the MYNXGRIP Closure Device during Repeated Transbrachial Percutaneous Peripheral Intervention - Klaus Hertting; Werner Raut (Case Reports in Vascular Medicine)
The use of closure devices after transbrachial arterial puncture is still controversial. Here we report on a case where the MYNXGRIP (AccessClosure Inc., Santa Clara, CA, USA) could be used successfully in a patient, who underwent percutaneous peripheral arterial intervention twice via transbrachial access.